Identification of pathogenic fungi - Campbell, Colin K.; Johnson, Elizabeth M. (Elizabeth Margaret), 1958-; Warnock, D. W. (Chichester, West Sussex : Wiley-Blackwell, 2013)
"A fully updated edition of this highly regarded textbook, incorporating new colour photographs of key species and their microscopic features, information on the latest antifungal drugs, and updated taxonomic information. Endorsed by the Health Protection Agency and written by world renowned experts in medical mycology"--Provided by publisher.
Machine generated contents note: 1. Introduction; life histories of the major groups of fungi and their spore types2. Identification of moulds; laboratory aspects of growing and examining moulds3. Moulds with aleuriospores I. The dermatophytes- Microsporum canis- Microsporum equinum- Microsporum gypseum- Microsporum fulvum- Epidermophyton floccosum- Trichophyston terrestre- Microsporum persicolor- Trichophyton equinum- Trichophyton erinacei- Trichophyton mentagrophytes- Trichophyton interdigitale- Trichophyton rubrum- Trichophyton rubrum (granular form)- Trichophyton tonsurans- Trichophyton soudanense- Microsporum audouinnii- Trichophyton schoenleinii- Trichophyton verrucosum- Trichophyton violaceum- Trichophyton concentricum- Other Microsporum and Trichophyton species4. Moulds with aleuriospores II. Others- Geomyces pannorm- Chrysosporium keratinophilum- Myceliophthora thermophia- Histoplasma capsulatum- Blastomyces dermatitidis- Paracoccidioides brasiliensis5. Moulds with holoblastic conidia- Aureobasidium pullulans- Sporothrix schenckii- Cladophialophora carrionii- Cladophialophora bantiana- Cladosporium sphaerospermum- Cladosporium herbarum- Cladosporium cladosporioides- Fonsecaea pedrosoi- Rhinocladiella atrovirens- Ramichloridium mackenziei- Ochroconis gallopava- Alternaria alternata- Ulocladium chartarum- Curvularia lunata- Bipolaris hawaiiensis- Bipolaris australiensis- Exserohilum rostratum- Exserohilum longirostratum- Exserohilum mcginnisii6. Moulds with enteroblastic conidia adhering in chains- Asergillus flavus- Aspergillus fumigatus- Aspergillus glaucus- Aspergillus nidulans- Aspergillus versicolour- Aspergillus ustus- Aspergillus niger- Aspergillus terreus- Aspergillus cadidus- Penicillium marneffei- Scopulariopsis brevicaulis- Paecilomyces lilacinus- Paecilomyces variotii7. Moulds with enteroblastic conidia adhering in wet masses- Cylindrocarpon lichenicola- Fusarium dimerum- Fusarium semitectum- Fusarium moniliforme- Fusarium oxysporum- Fusarium solani- Acremonium strictum- Acremonium kiliense- Lecythophora mutabilis- Lecythophora hoffmannii- Phialemonium spp.- Scedosporium prolificans- Scedosporium apiospermum- Phialophora parasitica- Phialophora richardsiae- Phialophora verrucosa- Phaeoannellomyces werneckii- Exophiala spinifera- Exophiala dermatitidis- Exophiala jeanselmei8. Mucoraceous moulds and their relatives- Cunninghamella bertholletiae- Absidia corymbifera- Rhizomucor pusillus- Mucor circinelloides- Rhizopus microsporus- Rhizopus arrhizus- Rhizopus stolonifer- Mucor hiemalis- Mucor racemosus- Basidiobolus ranarum- Conidiobolus coronatus- Pythium insidiosum- Apophysomyces elegans- Saksenaea vasiformis- Morierella wolfii9. Miscellaneous moulds- Aphanoascus fulvescens- Monascus ruber- Chaetomium globosum- Phoma herbarum- Myxotrichum deflexum- Schizophyllum commune- Leptosphaeria senegalensis- Neotstudina rosatii- Piedraia hortae- Lasiodiplodia theobromae- Pyrenochaeta romeroi- Pyrenochaeta unguis-hominis- Madurella mycetomatis- Madurella grisea11. Identification of yeasts- Candida albicans- Candida tropicalis- Candida krusei- Candida lipolytica- Candida kefyr- Candida lusitaniae- Candida parapsilosis- Candida pelliculosa- Candida glabrata- Candida guilliermondii- Cryptococcus neoformans- Rhodotorula glutinis- Saccharomyces cerevisiae- Geotrichum candidum- Blastoschizomyces capitatus- Trichosporon beigelii- Malassezia furfur- Malassezia pachydermatis-Appendices.
Revised edition of: Identification of pathogenic fungi / Colin K. Campbell [and others]. London : Public Health Laboratory Service, c1996.
Includes bibliographical references and index.
Print version record.
Keywords: Pathogenic fungi; Fungi; Fungi -- isolation & purification; Fungi -- pathogenicity; Mycoses -- diagnosis; SCIENCE -- Life Sciences -- Mycology; Fungi; Pathogenic fungi; Electronic books